African mahogany - Lamb, F. Bruce (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
African mahogany, formerly classified as belonging to the genus Swietenia, now belongs to the genus Khaya. This distinction is based on some secondary characteristics of the fruit and seed and the geographical distribution. However, there remains a doubt as to whether the African American mahoganies belong to different genera.